Ragam Penerjemahan - Kardimin Kardimin (Mukaddimah: Jurnal Studi Islam, 2018)
There are three issues that arise in the transition of text from the source language to the target language, ie translator, translation and translation. The translator is the actor who transfers ideas from the source language to the target language, whereas translation is a process done by someone in diverting the idea from the source language text into the target language text, while the translation as a resultant product, in the form of text either text or oral text . In the law of translation, we are familiar with relative truth. It means that there is no perfect translation. Truth in translation is subjective, relatively often temporal. It all depends on the purpose of translation was done (reading design). Therefore, it is only a work done by more than one translator. Thus, it can be predicted that the translation will be different from both the language style and the word choice used by each translator. This translation variation is often known as the variety or style. Thus, directly or indirectly, whether consciously or unconsciously, any translator will bring his or her own ideology. Ideology in the world of translation includes the ideology of foreignization and domestication. The ideology that departs from the techniques and methods used by the translator will have an impact on the quality of the translations produced.